Language Skills in Children with Attention Deficit Hyperactivity Disorder and Developmental Language Disorder: A Systematic Review - Inmaculada Méndez-Freije; Débora Areces; Celestino Rodríguez (Children, 2023)
(1) Background: Attention Deficit Hyperactivity Disorder (ADHD) and Developmental Language Disorder (DLD) are neurodevelopmental disorders that affect various areas of children’s development, such as language. It exists an emerging idea that ADHD is characterised by the presence of language difficulties, which can be explained by the high comorbidity between ADHD and DLD. The aim of this review is to analyse the empirical evidence of language competence in children aged 6–17 years old, diagnosed with ADHD and/or DLD. (2) Method: Fifteen studies with experimental designs were identified from Scopus, PsycINFO, and WoS databases, reporting on language skills in children diagnosed with ADHD and/or DLD. Studies relating executive functioning to language skills in this target population were also included. (3) Results: The literature is heterogeneous and different components of language are also examined. Even though the results are contradictory, they convincingly demonstrate there are overlapping symptoms between ADHD and DLD, such as language skills and executive functions. (4) Conclusions: The differences in the samples limit the generalisability of the results. Therefore, this review highlights the importance of considering language skills when designing individualised interventions for the population with ADHD and DLD, both in comorbidity and in isolation.